Compositional Study of Polymer Blend PVA, Pectin, Sodium Alginate, and Gelatin Electrospun Nanofiber for Wound Dressing Application - Jeng-Huang, Song; Lamandasa, Cynta Immanuela; Li, Chuan (Journal of Research Updates in Polymer Science, 2025)
Electrospun nanofibers are a biomaterial effective for wound healing due to their high surface area, tunable properties, and resemblance to the extracellular matrix. Nanofibers from the mixture of polymeric materials like gelatin, sodium alginate, pectin, and polyvinyl alcohol (PVA) were investigated in this study. Pectin, sodium alginate, and gelatin are selected for their nature of being applied as tissue carriers, and they have the properties of being biocompatible and biodegradable while inducing cell proliferation. Unfortunately, these polymers have some drawbacks: most of them have poor mechanical strength or poor processing ability through electrospinning. To enhance these properties, PVA was incorporated. The result showed that an optimal blend ratio of 20% PVA, 40% pectin, 25% sodium alginate, and 15% gelatin yielded a fibrous structure with an average diameter of the fibers equal to 174.82 ± 13 nm, surface tension of 33.29 mN/m, and viscosity at 7,378 cP, which facilitated the uniform fiber formation and a porous structure for enhanced gas exchange and moisture retention, significantly aiding wound healing.